RESISTENSI KELOMPOK MASYARAKAT LOKAL ATAS PENGELOLAAN SUMBER DAYA HUTAN DI KABUPATEN MUNA - La Ode Topo Jers (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2016)
This research is about the resistance of local society groups to the management of forest resources carried out in protected forest areas of Muna Regency, one of the areas known as teak producers. This research used ethnographic methods and analysis to analyze the forest damage related to land tenure within forest area by farmer group. This study looked at the opposition of group of society to the government in the management of natural resources that were the source of the economy and welfare for the local people in Muna. Land tenure conflicts by farming groups within state forest areas are becoming increasingly out of control and not well resolved between society and governments. This resistance was been assumed as a result of the disappointment of the people especially the people who living around the forest area on the state policy on the management of natural resources, especially forests. According to the society, the management of natural resources in the field of forestry was considered undemocratic, centralized so it was not to the side of the local society as the aggrieved party. Forest management policies that did not bring benefit to the people were perceived as unfair, resulting gaps and social resistance actions from society groups living around protected forest areas in Muna. Keywords: management of forest, society, policies, resistance